A gestão nas agroindústrias exportadoras de amêndoas de castanha-de-caju no estado do Ceará - Chrisóstomo, Evangelina (2008)
This study approaches Brazilian cashew nuts agrindustry exportation management in Ceara, within their production, industrialization and marketing areas. Such production creates about 40 thousand jobs in country and about 15 to 20 thousand jobs in industry. Cashew nut is also the first product in exportation agenda in Ceara. The descriptive research was carried out by means of a field research with Brazilian cashew nuts agribusiness exportation managers, with a survey which used Likert scale in some questions. Variables in the survey were part of the so called management process group (planning, execution and control), and factors that could damage company`s management, such as: starting material acquisition and stocking, production factors, market factors, and commercialization constraints for cashew nuts exportation. Results show that Brazilian cashew nuts agribusiness exportation in Ceara proceed to strategic planning, control starting material acquisition and sorting, there is starting material traceability and control from integrated systems.